2018
DOI: 10.7600/jpfsm.7.185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamification-based intervention for promoting health behaviors

Abstract: The purposes of this study were to examine the effectiveness of the gamificationbased intervention on health behavior change. Participants were 53 Japanese undergraduate and graduate students, of whom 30 were allocated to the intervention group and 23 were allocated to the control group. In the intervention group, daily physical activity and dietary behavior were assessed using a mobile phone application called The Way of Health. The application includes various functions, such as recording daily steps and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In contrast, GBL takes place only during specific periods of time because it usually focuses on a game designed with the primary objective of learning rather than entertaining [25]. Gamification has been a trending topic in different domains of knowledge such as health promotion [26][27][28], online programs [29], internet intervention [30], and education [31][32][33][34][35][36][37]. Therefore, the terms defined above are not synonymous but describe different valid approaches in the educational context that should not be confused because their focus and purpose are not the same [23,38].…”
Section: Games and Gamificationmentioning
confidence: 99%
“…In contrast, GBL takes place only during specific periods of time because it usually focuses on a game designed with the primary objective of learning rather than entertaining [25]. Gamification has been a trending topic in different domains of knowledge such as health promotion [26][27][28], online programs [29], internet intervention [30], and education [31][32][33][34][35][36][37]. Therefore, the terms defined above are not synonymous but describe different valid approaches in the educational context that should not be confused because their focus and purpose are not the same [23,38].…”
Section: Games and Gamificationmentioning
confidence: 99%
“…Gamification is another way fitness trackers may work to reduce SB. Gamification is defined as applying game mechanics to contexts that are typically not seen as a game [28]. For example, gamification in PA can be viewed as step challenges over a seven-day period where a higher number of steps increases one's chances of "winning".…”
mentioning
confidence: 99%
“…For example, gamification in PA can be viewed as step challenges over a seven-day period where a higher number of steps increases one's chances of "winning". Gamification boosts user engagement in PA, where points, badges, and leaderboards have been seen to be highly effective motivators [28]. A recent study showed that users' step counts increased by 23% during a step competition compared to the baseline [29].…”
mentioning
confidence: 99%
See 2 more Smart Citations